Reservoir Architecture in Tide-Dominated Estuary: A Case Study of McMurray Formation Oil Sand Reservoir in the Athabasca Block, Canada - Zhang, Weixue; Huang, Jixin; Feng, Wenjie; Wang, Lixin; Shang, Haojie; Yin, Yanshu (Frontiers in Earth Science, 2022)
Tidal-dominated estuaries were affected by bidirectional water flow, sea level fluctuations, and paleo-geomorphic, which formed complex sedimentary systems, resulting in complex reservoir architecture characteristics. Therefore, it is necessary to understand the reservoir architecture characteristics in estuaries to support the exploration and development of oil and gas resources. This study used core data, logging data, high-quality 3D seismic data to characterize the reservoir architecture of the McMurray Formation by using the reservoir architectural element analysis method, and the characteristics of the reservoir architecture and the evolution of the reservoir elements were clarified in the tide-dominated estuary. Nine architecture elements were found in the core observation, which were channel, salt marsh, estuary point bar, tidal point bar, mud flat, mixed flat, sand flat, tidal bar and offshore. The interpretation of the 3D seismic data showed that the stratum had frequent incised, which related to the changes of sea level. Tidal bars were developed in the incised valleys, which have lateral characteristics and were deposited in contact with the sand flats. The contact deposition of tidal bar and sand flat forms a special reservoir architectural pattern, which is a high-quality reservoir in the study area. Architectural anatomy is helpful to predict the internal structure of tidal sand bars and tidal flats, deduce the evolution process of tidal estuary, and better guide the oil and gas exploration and development of estuary reservoir.